Creating Mosquito Larvae-Free Villages through Mentoring and Training Making Mosquito Repellent Liquid and 3M Plus National Population Monitoring Program (PSN): Mewujudkan Desa Bebas Jentik Nyamuk melalui Pendampingan dan Pelatihan Pembuatan Cairan Anti Nyamuk dan PSN 3M Plus - Budi Yulianto; Lilis Prihastini; Aries Prasetyo; Nurlailis Saadah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Dengue Hemorrhagic Fever (DBD) remains a public health problem that requires an integrated control strategy. Community empowerment through community participation is an effective approach in preventing and eradicating this disease. Community service activities in Ngiliran Village were carried out by providing training and mentoring to health cadres, mosquito larvae control cadres, housewives, and youth organizations (ILP cadres – Primary Service Integration). Training materials included the implementation of PSN (Mosquito Nest Eradication) 3M (draining and closing water tanks, recycling/burying used goods) Plus, making natural mosquito repellent liquid, understanding the symptoms and dangers of DBD, and efforts to create a healthy home environment. Implementation methods included counseling, product manufacturing practices, and cross-sector advocacy involving community leaders, religious leaders, and local social organizations. The results of the activity demonstrated an increase in participants' knowledge and skills in dengue fever prevention and control, the development of a mosquito repellent product made from lemongrass and orange peel, and the revitalization of the roles of Pokjasan (health working groups), Jumantik (larvae monitors), and village cadres. This activity demonstrated that a community-based, participatory approach, combined with ongoing training and mentoring, can increase community capacity in dengue fever control efforts.